Plastidial acyl carrier protein Δ9‐desaturase modulates eicosapentaenoic acid biosynthesis and triacylglycerol accumulation in Phaeodactylum tricornutum. (5th May 2021) - Smith, Richard; Jouhet, Juliette; Gandini, Chiara; Nekrasov, Vladimir; Marechal, Eric; Napier, Johnathan A.; Sayanova, Olga
SUMMARY: The unicellular marine diatom Phaeodactylum tricornutum accumulates up to 35% eicosapentaenoic acid (EPA, 20:5n3) and has been used as a model organism to study long chain polyunsaturated fatty acids (LC‐PUFA) biosynthesis due to an excellent annotated genome sequence and established transformation system. In P. tricornutum, the majority of EPA accumulates in polar lipids, particularly in galactolipids such as mono‐ and di‐galactosyldiacylglycerol. LC‐PUFA biosynthesis is considered to start from oleic acid (18:1n9). EPA can be synthesized via a series of desaturation and elongation steps occurring at the endoplasmic reticulum and newly synthesized EPA is then imported into the plastids for incorporation into galactolipids via an unknown route. The basis for the flux of EPA is fundamental to understanding LC‐PUFA biosynthesis in diatoms. We used P. tricornutum to study acyl modifying activities, upstream of 18:1n9, on subsequent LC‐PUFA biosynthesis. We identified the gene coding for the plastidial acyl carrier protein Δ9‐desaturase, a key enzyme in fatty acid modification and analyzed the impact of overexpression and knock out of this gene on glycerolipid metabolism. This revealed a previously unknown role of this soluble desaturase in EPA synthesis and production of triacylglycerol. This study provides further insight into the distinctive nature of lipid metabolism in the marine diatom P. tricornutum and suggests additional approaches for tailoring oil composition in microalgae. Significance Statement: In the marine diatom Phaeodactylum tricornutum, the main chloroplast lipids are enriched in eicosapentaenoic acid (EPA) despite its synthesis on the endoplasmic reticulum. We show that committed EPA biosynthesis commences with the action of a plastidial acyl carrier protein Δ9‐ desaturase, using palmitic acid (16:0) as substrate. Targeted mutagenesis of this gene leads to an EPA increase and decreased triacylglycerol, providing evidence that this plastidial enzyme acts as a gating enzyme for extraplastidial EPA and triacylglycerol production.